The problem of locating the battle of 1223 between the Mongols and the Volga Bulgars - Stavitsky V.V. (Золотоордынское обозрение)
Research objectives: To clarify the localization and circumstances of the battle that took place in 1223 between the Mongols and the Volga Bulgars. Research materials: Data from the Complete History of Ibn al-Asir, Russian chronicles, archaeological materials of Zolotarevsky settlement are analyzed, hypotheses of Russian historians are considered: A.Kh. Khalikov, L.N. Gumilev, I.L. Izmailov and others. Research results and scientific novelty: The 800 years since the battle of Volga Bulgars with Mongols is celebrated this year. Direct information about the battle is contained only in the work of Ibn al-Asir. Geographical coordinates of the battle are absent; it is only recorded that it took place when the Mongols approached the city of Bulgar. A.Kh. Khalikov suggested that the battle took place in the Volga region, near Samarskaya Luka. L.N. Gumilev believed that the Mongols were defeated at the crossing of the Volga, but this point of view does not agree with the data provided by Ibn al-Asir. I.L. Izmailov came to the conclusion that the battle took place on the, Upper Sura in the vicinity of the Zolotarev settlement where a significant collection of elite Mongol armament was gathered. The settlement was on a trade way from Bulgar to Kiev. Therefore, if the Mongols went from the territory of the Don region, they could hardly pass it. However, according to Chinese and Old Russian sources, the main goal of the Mongols was to defeat the Cumans. In pursuit of them they had to go to Saksin and only from there turn to the north. In the message of Ibn al-Asir there is a figure of 4 thousand Mongol warriors. A number of historians believe that it refers only to the number of troops who retreated to Saksin, but more likely is the assumption that this is the number of those who died in the battle. In this connection, only the vanguard detachment pursuing the Polovtsians was defeated in the battle.